Computational Simulation and Modeling of Freak Waves Based on Longuet-Higgins Model and Its Electromagnetic Scattering Calculation - Gengkun Wu; Chuanxi Liu; Yongquan Liang (Complexity)
In order to solve the weak nonlinear problem in the simulation of strong nonlinear freak waves, an improved phase modulation method is proposed based on the Longuet-Higgins model and the comparative experiments of wave spectrum in this paper. Experiments show that this method can simulate the freak waves at fixed time and fixed space coordinates. In addition, by comparing the target wave spectrum and the freak wave measured in Tokai of Japan from the perspective of B-F instability and spectral peakedness, it is proved that the waveform of the simulated freak waves can not only maintain the spectral structure of the target ocean wave spectrum, but also accord with the statistical characteristics of the wave sequences. Then, based on the Kirchhoff approximation method and the modified Two-Scale Method, the electromagnetic scattering model of the simulated freak waves is established, and the normalized radar cross section (NRCS) of the freak waves and their background sea surfaces is analyzed. The calculation results show that the NRCS of the freak waves is usually smaller than their large-scale background sea surfaces. It can be concluded that when the neighborhood NRCS difference is less than or equal to −12 dB, we can determine where the freak waves are.